The Outcome-Based Education through Integrated Learning to Enhance English Communication Skills - Neni Triana; Fenny Anita (Global Expert: Jurnal Bahasa dan Sastra, 2026)
In the era of globalization and rapid digital transformation, English communication skills have become an essential competency for university students to succeed in both academic and professional contexts. However, many students still experience difficulties in developing effective communication skills, particularly in speaking, due to limited opportunities for practice and the persistence of traditional, theory-based instructional methods. This study aims to identify and synthesize teaching and learning strategies aligned with the principles of Outcome-Based Education (OBE) and their contribution to enhancing English communication skills in higher education. This study employed a qualitative approach using a Systematic Literature Review (SLR) design. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure transparency, replicability, and methodological rigor in identifying, screening, and selecting relevant studies. PRISMA has been widely recognized as a standard framework for systematic reviews across disciplines, including education, due to its structured and comprehensive process. In addition, recent educational research has increasingly adopted PRISMA to examine instructional strategies, curriculum development, and pedagogical innovation in higher education. Data were collected from reputable databases and analyzed using thematic synthesis. The findings reveal that the integration of multiple learning strategies—such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), Task-Based Language Teaching (TBLT), Communicative Language Teaching (CLT), role play and simulation, and collaborative learning—significantly enhances students’ engagement and English communication competence. These strategies provide authentic, student-centered, and contextual learning experiences that enable active language use. Furthermore, constructive alignment between learning outcomes, instructional activities, and assessment is essential in ensuring the effectiveness of OBE implementation Keywords: Outcome-Based Education, Systematic Literature Review, English communication skills, learning strategies, higher education